Polymorphisms in MEN1 and DRD2 genes are associated with the occurrence and characteristics of pituitary adenomas. Issue 2 (August 2016) - Peculis, Raitis; Balcere, Inga; Rovite, Vita; Megnis, Kaspars; Valtere, Andra; Stukens, Janis; Arnicane, Ligita; Nikitina-Zake, Liene; Lejnieks, Aivars; Pirags, Valdis; Klovins, Janis
Abstract : Objective: Although pituitary adenomas (PAs) affect a significant proportion of the population, only a fraction have the potential to become clinically relevant during an individual's lifetime, causing hormonal imbalance or complications due to mass effect. The overwhelming majority of cases are sporadic and without a clear familial history, and the genotype–phenotype correlation in PA patients is poorly understood. Our aim was to investigate the involvement of genes known for their role in familial cases on drug response and tumor suppression in the development and pathology of PAs in a patient group from Latvia. Design: The study included 143 cases and 354 controls, we investigated the role of single-nucleotide polymorphisms (SNPs) in seven genes ( SSTR2, SSTR5, DRD2, MEN1, AIP, GNAS, and PRKAR1A ) associated with pituitary tumor occurrence, phenotype, and clinical symptoms. Methods: Genotyping of 96 tag and nonsynonymous SNPs was performed in the genomic regions of interest. Results: We discovered a significant association (OR=17.8, CI 0.95=2.18–145.5, P =0.0002) between a rare MEN1 mutation (rs2959656) and clinically active adenoma in our patients. Additionally, rs7131056 at DRD2 was associated with a higher occurrence of extrasellar growth in patients with prolactinoma and somatotropinoma (OR=2.79, CI 0.95=1.58–4.95, P =0.0004). Conclusions: rs2959656, a nonsynonymous variant in MEN1, is associated with the development of clinically active PA. Furthermore, rs7131056 in DRD2 contributes to either faster growth of the adenoma or reduced symptomatic presentation, allowing PAs to become larger before detection.